2019
DOI: 10.2147/nss.s222359
|View full text |Cite
|
Sign up to set email alerts
|

<p>Poor Sleep Quality Associated With High Risk Of Ventricular Tachycardia After Acute Myocardial Infarction</p>

Abstract: BackgroundSleep disorders (SDs) are usually associated with an increase in frequency of ventricular tachycardia (VT). However, the relationship between SDs and the prevalence of VT within the first week of acute myocardial infarction (AMI) remains unclear. This study aimed to evaluate their associations and potential mechanisms.MethodsThis structured questionnaire-based cross-sectional study enrolled 303 patients with AMI from a hospital in northern China. Pittsburgh Sleep Quality Index (PSQI) was used to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…Meanwhile, our previous study showed that the imbalance between sympathetic and parasympathetic nerves plays a vital role in constipation symptoms ( Liu et al, 2020 ). Notably, the current study showed that sleep disorders will influence the balance between parasympathetic and sympathetic nerves thus remarkably increasing sympathetic activities, which is similar outcomes to previous research ( Carter et al, 2018 ; Wang S. et al, 2019 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Meanwhile, our previous study showed that the imbalance between sympathetic and parasympathetic nerves plays a vital role in constipation symptoms ( Liu et al, 2020 ). Notably, the current study showed that sleep disorders will influence the balance between parasympathetic and sympathetic nerves thus remarkably increasing sympathetic activities, which is similar outcomes to previous research ( Carter et al, 2018 ; Wang S. et al, 2019 ).…”
Section: Discussionsupporting
confidence: 91%
“…It has been reported that poor sleep will lead to sympathetic activation. Wang S. et al (2019) reported that poor sleep would increase the LF/HF ratio and make LF higher, reflecting increased sympathetic activity and decreased parasympathetic activity. Carter et al (2018) reported that individuals with chronic insomnia exhibit increased sympathetic neural as well as cardiovascular reactivity to stress, augmented sympathetic neural outflow, and blunted baroreflex sensitivity relative to good-sleeper individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence of patients with poor sleep quality (ie, 51%) in the Oliveira‐Sousa study was similar to that reported by Wang et al in acute myocardial infarction 11 and raises the question of whether this sample reflects the real burden of sleep disturbances in the community. Data from the 2007 to 2008 National Health Nutrition Examination Survey ( NHANES) targeting the prevalence of sleep symptoms have shown that long sleep latency, self‐reported difficulty in falling asleep, sleep maintenance difficulties, and early morning awakenings were reported by more than 50% of the participants 15 .…”
supporting
confidence: 78%
“…Some previous studies evaluating the effect of global sleep status on cardiac autonomic function, as assessed by HR variability and catecholamine levels, have been carried out in patients with cardiovascular disease (ie, acute myocardial infarction). In this critical setting, higher levels of adrenaline and norepinephrine, a significant increase in low‐frequency power as well as low‐frequency/high‐frequency power ratio and reduced high‐frequency power were found in 147 patients (61% men) with poor sleep quality as compared to their counterparts with good sleep quality (n = 156, 67% men) 11 . In clinical terms, sympathetic hyperactivity, associated with short‐lasting poor sleep quality, resulted in increased prevalence of ventricular tachycardia in the following week after acute myocardial infarction.…”
mentioning
confidence: 97%
See 1 more Smart Citation